2021
DOI: 10.3390/agronomy11071327
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Harvesting Time on Phenolic and Mineral Profiles and Their Association with the Antioxidant and Cytotoxic Effects of Atractylodes japonica Koidz

Abstract: Plant phytochemical accumulation is influenced by various external factors that change with the seasons (e.g., harvesting time). Atractylodes japonica, an important medicinal plant rich in bioactive compounds, is used to treat several human diseases. We analyzed the influence of harvesting time on phenolic compound concentration and antioxidant activity of A. japonica roots. We investigated the correlation between phenolic compound and minerals contents and antioxidant activity in different harvests. Total phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…At the third harvest, the white mugwort treated all three chicken manure dosages had the highest total phenolic content (11.26–11.77 mg gallic acid equivalents g -1 fresh weight), while the white mugwort treated with chicken manure at medium and high dosage rates showed the highest DPPH radical scavenging activity (1.59–1.65 μmol TEAC g -1 fresh weight) (Figs 3 and 4 ). According to the report by Ghimire et al [ 43 ], there is a positive correlation between micronutrients including Zn and Mn in plant tissues and the phenolic compounds of Atractylodes japonica Koidz. The higher total phenolic content in chicken manure treated plants with the longer harvesting time in this study may be explained by the greater opportunity for chicken manure micronutrient take-up, as it was applied after each harvesting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the third harvest, the white mugwort treated all three chicken manure dosages had the highest total phenolic content (11.26–11.77 mg gallic acid equivalents g -1 fresh weight), while the white mugwort treated with chicken manure at medium and high dosage rates showed the highest DPPH radical scavenging activity (1.59–1.65 μmol TEAC g -1 fresh weight) (Figs 3 and 4 ). According to the report by Ghimire et al [ 43 ], there is a positive correlation between micronutrients including Zn and Mn in plant tissues and the phenolic compounds of Atractylodes japonica Koidz. The higher total phenolic content in chicken manure treated plants with the longer harvesting time in this study may be explained by the greater opportunity for chicken manure micronutrient take-up, as it was applied after each harvesting.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that other factors may play a role in total phenolic content and DPPH radical scavenging activity of the white mugwort. Several studies show a correlation between total phenolic content and DPPH radical scavenging activity under other environmental conditions, such as precipitation, humidity, and solar radiation intensity [ 43 , 45 ]. To support this, Kałużewicz et al [ 46 ] revealed that the concentration of phenolic content in cauliflower is significantly increased with the amount of irrigation water.…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemicals in the plant can differ significantly depending on the environmental factors such as temperature, humidity, and precipitation. [35][36][37] Of the phytochemicals, eugenol and hydroxychavicol are one of the most widely considered responsible for the antibacterial properties of P. betle. In the Philippines, eugenol was reported while hydroxychavicol has not been identified yet.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies have shown that the bark of G. tessmannii contained flavonoids, triterpenes, sterols, alkaloids, tannins and polyphenols (Koumba et al, 2019;Deeh Defo et al, 2018). The environment, organ harvesting periods, organ storage conditions and extraction solvents can influence the synthesis and expression of plant phytochemical components (Bimal et al, 2021). Antioxidants present in G. tessmannii are part of the therapeutic arsenal of arteriosclerosis and cancers that are the facilitators of high blood pressure (Sorriento et al, 2018).…”
Section: Antioxidant Activitiesmentioning
confidence: 99%